EVALUATING THE IMPLEMENTATION OF THE PANCASILA STUDENT PROFILE STRENGTHENING PROJECT IN A VOCATIONAL HIGH SCHOOL: A CIPP EVALUATION FRAMEWORK - Abdurrasyid Ridha; Hidayani Syam; Rira Jun Fineldi (Universitas HKBP Nommensen, 2026)
This study aims to examine the implementation of the Pancasila Student Profile Strengthening Project (P5) within the Merdeka Curriculum at SMK Negeri 1 Batipuh using the Context, Input, Process, and Product (CIPP) evaluation model. A qualitative approach with an evaluative design was employed to obtain an in-depth understanding of how the program is carried out in the school setting. The participants included the principal, teachers, and educational staff who were directly involved in the implementation of the P5 program. Data were collected through observations, semi-structured interviews, and document analysis. The data analysis process involved data reduction, data display, and interpretative conclusion drawing, while data validity was ensured through source and method triangulation. The findings indicate that the implementation of the P5 program has been relatively effective. From the context perspective, the program is supported by Merdeka Curriculum policy and is integrated into the school’s vision and strategic programs. In terms of input, the availability of human resources and facilities is considered adequate, although further improvement in teachers’ competencies in project-based learning is still necessary. Regarding the process component, the program is implemented through collaborative learning activities that promote active student participation, creativity, and critical thinking skills. From the product perspective, the program contributes positively to students’ character development, teamwork, and communication skills. These findings suggest that the CIPP model provides a comprehensive framework for evaluating character-based educational programs and highlight the importance of strengthening teacher capacity, improving program management, and conducting continuous evaluation to enhance the quality of P5 implementation.